Restorative Justice-Based Law Enforcement of Corruption by Village Officials: A State Loss Returns Perspective - I Made Bagus; Kiki Kristanto; Claudia Yuni Pramita (Rechtenstudent, 2025)
The increase in Village Fund allocation since 2015 aims to accelerate development and empower rural communities. However, this has also triggered rampant corruption by village officials, which has had a serious impact on state financial losses and hampered development. To date, the law enforcement approach used has been retributive, focusing on criminalizing perpetrators without providing optimal solutions for recovering state losses. This study aims to examine the relevance of implementing restorative justice as an alternative law enforcement approach to corruption by village officials, with a focus on actually recovering state losses. The research method used is normative juridical with a statutory and conceptual approach, and examines the principles of restorative justice and the theory of economic analysis of law. The results of the discussion indicate that the implementation of restorative justice can be a more responsive legal strategy to the need for recovery of state losses, as long as it is carried out within the corridors of positive law, transparency, and community participation.